2021
DOI: 10.1515/jpem-2020-0714
|View full text |Cite
|
Sign up to set email alerts
|

Liraglutide combined with intense lifestyle modification in the management of obesity in adolescents

Abstract: Objectives Childhood obesity is a public health concern worldwide, with rates continuing to rise, despite preventive measures. Lifestyle modification remains the mainstay in the treatment of patients with excessive weight, but unfortunately, this is not always successful. Options for medical management of obesity in the paediatric population are limited. Methods Seven adolescents (all girls, mean age 14.9 years) with a body m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 21 publications
0
8
0
Order By: Relevance
“…Patients exhibited a lack of adherence to lifestyle modifications, a crucial factor identified for achieving significant weight loss in previous research [ 20 ]. Despite conducting an initial consultation on lifestyle modifications, patients lost motivation to adhere to lifestyle interventions when weight loss was not observed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Patients exhibited a lack of adherence to lifestyle modifications, a crucial factor identified for achieving significant weight loss in previous research [ 20 ]. Despite conducting an initial consultation on lifestyle modifications, patients lost motivation to adhere to lifestyle interventions when weight loss was not observed.…”
Section: Discussionmentioning
confidence: 99%
“…Many participants displayed a significant psychological connection to food, highlighting the potential benefit of including a psychologist in the team. Apperley et al [ 20 ] conducted a study with an intense weight management program with liraglutide. The participants were reviewed by a multidisciplinary team (MDT) every two weeks for advice and support and treated with daily subcutaneous injections of liraglutide (dose range 1.2-3.0 mg).…”
Section: Discussionmentioning
confidence: 99%
“…Concerning liraglutide, it is an agonist of the human GLP-1 receptor, which plays an essential role in the resistance to obesity [ 48 , 49 ]. Numerous clinical trials have observed that the administration of liraglutide at 3.0 mg per day to obese patients and most importantly, accompanied by a change in lifestyle, significantly reduces visceral adipose tissue over 40 weeks of treatment [ 50 , 51 , 52 ].This study was conducted following the Delphi methodology, which inherently presents limitations in validity and reliability. It is a very laborious process that requires at least two rounds to obtain an adequate consensus, subjective criteria are developed that are subject to external influences from the participants, and there may be confusion in the interpretation of the content of some questions.…”
Section: Discussionmentioning
confidence: 99%
“…A recent UK‐based study has shown that when combined with an intense weight management programme, patients treated with liraglutide dropped BMI by 2.1 kg/m 2 over a period of 3 months. Liraglutide was shown to be well tolerated by all patients receiving the treatment 78 . Liraglutide has also shown promise as a potential therapeutic option in treatment‐resistant obesity by Kochar et al 74 Adolescents with obesity which was initially managed by lifestyle changes and then oral medications but had failed to achieve weight loss, were trialled on liraglutide for 12 weeks 74 .…”
Section: Definitionmentioning
confidence: 99%